2019
DOI: 10.1111/ddi.12958
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating stakeholder‐derived strategies to reduce the risk of ships striking whales

Abstract: Aim: Ship strikes are one of the largest sources of human-caused mortality for baleen whales on the West Coast of the United States. Reducing ship-strike risk in this region is complicated by changes in ship traffic that resulted from air pollution regulations and economic factors. A diverse group of stakeholders was convened to develop strategies to reduce ship-strike risk in the Southern California Bight. Strategies proposed by some stakeholders included: (a) adding a shipping route; (b) expanding the existi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 28 publications
0
24
1
Order By: Relevance
“…Moore et al (2018) used Conn and Silber's (2013) equation relating ship speed to the probability that a ship strike is fatal to estimate that reductions in ship speeds in the Santa Barbara Channel (i.e., the 2008 traffic pattern in the southern California region; Figure 1) represent a 20% reduction in the probability of a fatal strike. Consequently, ship speeds should be considered when designing strategies that can mitigate risk (e.g., Redfern et al, 2019). Our analyses show that static, spatial management strategies can be used to mitigate ship-strike risk from nearshore versus offshore traffic off California.…”
Section: Finmentioning
confidence: 93%
See 3 more Smart Citations
“…Moore et al (2018) used Conn and Silber's (2013) equation relating ship speed to the probability that a ship strike is fatal to estimate that reductions in ship speeds in the Santa Barbara Channel (i.e., the 2008 traffic pattern in the southern California region; Figure 1) represent a 20% reduction in the probability of a fatal strike. Consequently, ship speeds should be considered when designing strategies that can mitigate risk (e.g., Redfern et al, 2019). Our analyses show that static, spatial management strategies can be used to mitigate ship-strike risk from nearshore versus offshore traffic off California.…”
Section: Finmentioning
confidence: 93%
“…Consequently, more detailed and fine-scale analyses are needed to design strategies that can mitigate risk for all species in these regions. For example, Redfern et al (2019) developed methods to estimate ship-strike risk in strategies proposed by stakeholders to reduce risk in the Southern California Bight and found that speed reductions and expanding the existing area to be avoided may provide an optimal solution for addressing stakeholder needs and reducing ship strikes. Analyses are also needed to address risk from January-June because studies have found seasonal changes in fin (Scales et al, 2017) and humpback (Becker et al, 2017) whale distributions off California.…”
Section: Finmentioning
confidence: 99%
See 2 more Smart Citations
“…Correlative SDMs associate species presence or presence-absence data with environmental predictor variables, fit a relationship between predictor and response, and make predictions for an area of interest (Redfern et al, 2006). These types of SDMs have been used to conduct near real-time monitoring (Abrahms et al, 2019;Hazen et al, 2017) and address a number of conservation challenges, including evaluating and mitigating ship-strike risk (Redfern, Becker, & Moore, 2020;Redfern et al, 2019), and they have shown potential in forecasting species distributions (Becker et al, 2018). Many studies that model marine animal density or distributions use oceanographic proxies for prey (e.g., Becker et al, 2016;Redfern et al, 2006;Sequeira, Mellin, Rowat, Meekan, & Bradshaw, 2012), which is expected to be the true driver of species' migratory phenology and their distribution on foraging grounds.…”
Section: Introductionmentioning
confidence: 99%